2008
DOI: 10.1128/jcm.01438-07
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Accessory Gene Patterns Predicts the Same Relatedness among Strains of Streptococcus pneumoniae as Sequencing of Housekeeping Genes Does and Represents a Novel Approach in Molecular Epidemiology

Abstract: Relatedness between isolates of Streptococcus pneumoniae can be determined from sequences of multiple genes belonging to the core genome (multilocus sequence typing [MLST]), but these do not provide information on gene content that may affect the potential of isolates to cause invasive pneumococcal disease. Gene content data, obtained using microarrays, were gathered for 40 clinical isolates of 12 serotypes belonging to 30 multilocus sequence types. We found that sequence variations in housekeeping genes asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…Multilocus sequence typing (MLST) and multilocus sequence analysis (MLSA) utilize the concept of genetic evolution at multiple conserved genes to measure evolutionary distances between species or strains (81-83). These conserved ("housekeeping") genes are required for the basic functions of the cell and must be found in all bacteria in the comparison (84)(85)(86). Examples of housekeeping genes used in classifying Pseudomonas species include rpoD (-subunit of RNA polymerase), rpoB (␤-subunit of RNA polymerase), and gyrB (␤-subunit of gyrase, responsible for negative supercoiling of DNA during replication) (80,87,88).…”
Section: Taxonomy and Genomics Of The Pseudomonas Genus And The P Flmentioning
confidence: 99%
“…Multilocus sequence typing (MLST) and multilocus sequence analysis (MLSA) utilize the concept of genetic evolution at multiple conserved genes to measure evolutionary distances between species or strains (81-83). These conserved ("housekeeping") genes are required for the basic functions of the cell and must be found in all bacteria in the comparison (84)(85)(86). Examples of housekeeping genes used in classifying Pseudomonas species include rpoD (-subunit of RNA polymerase), rpoB (␤-subunit of RNA polymerase), and gyrB (␤-subunit of gyrase, responsible for negative supercoiling of DNA during replication) (80,87,88).…”
Section: Taxonomy and Genomics Of The Pseudomonas Genus And The P Flmentioning
confidence: 99%
“…A similar methodology has recently been described for typing Streptococcus pneumoniae (11), Campylobacter jejuni (49), and Escherichia coli strains (47), suggesting that this approach is likely to be useful in the development of next-generation genotyping methods. Subsequent iterations of VAP analysis targeting additional loci will be derived from new E. coli O157:H7 sequence data as they become available.…”
mentioning
confidence: 99%
“…PFGE is more discriminatory than MLST and can be used also to study outbreaks. Furthermore, genomic comparisons using whole genome-based microarrays have shown that MLST can be used as a good method to estimate genome content (Dagerhamn et al 2008).…”
Section: Epidemiologymentioning
confidence: 99%